Comparison between the Effects of Alcohol and Hexane Extract of Spirulina in Arsenic Removal from Isolated Tissues (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):27-31.The abstract of this article is available on the PubMed website